The Effect of Capital Structure on the Performance of Selected Conglomerates in Nigeria - John Ime John (Law and Economy, 2022)
This study focused on the effect of capital structure performance in Nigeria conglomerates. It sought to assess the significance of capital structure, and to suggest measures that could enhance its effectiveness and firms’ performance in Nigeria. To achieve the objective of the research, some financial and performance indicators, using an ex-post facto research design was applied. The population of the study comprised of six (6) firms. The data was collected, analyzed and tested using the descriptive statistics and the panel data analysis techniques. From the analysis, it was revealed that there was a significant relationship between debt ratio and conglomerates performance in Nigeria. Also, it was revealed that long term debt to capital employed had a significant influence on conglomerates performance in Nigeria. Furthermore, total debt ratio was found to have a significant effect on conglomerates performance in Nigeria. Based on the findings, the study recommended that the management of Nigerian conglomerates should work very hard to optimize their capital structure, in order to increase the financial performance. They can do that through ensuring that the debt proportion (debt ratio) in their capital structure is optimal. Also, the Management of Nigerian conglomerates should increase their commitments into long term debt to capital employed, in order to improve financial performance from their business operation.